Pengaruh Pemberian Tepung Daun Kelor (Moringa Oliefera) pada Ibu Hamil terhadap Berat Badan Bayi Baru Lahir - Hafid, Rachmawati Abdul (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the effect of kelor leaf meal (moringa oliefera) in pregnant women to newborn weight. Research Methodology: Quantitative research type with research type true experiment Design used is Randomized Double Blind, postestcontrolled. The sample in this study of pregnant women with third trimester of gestational age 28 weeks as many as 38 people divided into 2 groups. Pregnant women given kelor leaf capsules are the intervention group and the unemployed mother who is not given iron (Fe) capsule is a control group. Birth weight measurement was performed after intervention 60 days later post-test weighing newborn weight. Provision of intervention conducted for 60 days with a dose of 2 times 2 capsules a day. Newborn's weight sample will be weighed using baby scale. Data analysis was performed with Mann Whitney Test. Result: The results showed that there was a difference of birth weight between intervention group and control group with p-value 0,004. The mean value of post-test in the intervention group was 3389.47 While in the control group the mean value of post-test 3000. From the results of the study it can be concluded that the application of kelor leaf capsules more effectively increase the baby's weight compared to the control group.